Online strategies for offline business the case of Millennials and shopping centrs (Sonae Sierra) - Kotzaeroglou, Aliki (2016)
The project, conducted within a direct research internship at Sonae Sierra, aims to propose innovative digital approaches for Shopping Centres (SC) to deal successfully with millennial consumer behavior concerning digital devices and online content in relation to shopping. An online survey followed by a focus group were conducted for this purpose. Results show a demand for specific digital services created by a SC and that their perception depends highly on gender of millennials. Moreover it´s a cohort seeking for personalized content, providing emotional or functional benefit. Consequently a SC must deliver services, as presented in this work satisfying those needs.